Computerized Histopathological Image Analysis: A review on Multiple Instances - Gaikwad, Vilas S; Holambe, Anilkumar N (International Journal of Computer Sciences and Engineering, 2025)
This review paper deals with the most recent expertise developed on Digital assisted examination for histopathology images. The development on digital assisted examination for locating, analyzing and classification of fatal diseases like cancer, using histopathology. The previously, the observer is completely based on the proficiency level of the pathologist, is done by the physical processes. The organizational structure of the analysis of digital slides, cell distribution and the shape of the cell is based on the action. The entire interior of this process informal for the observer as well as the external observer. Histopathological diagnosis of tissue-paper images from the quantitative analysis of the process to evaluate the computerized Image. Histopathology of digital image processing techniques that can be applied to the area of digital slide analysis is presented in the summary. Histopathology of discrimination in the automated retrieval of the digital slides is an important area of research in image processing.